MASALAH PELAKSANAAN TUGAS JURU SITA DALAM PROSES PERKARA PERDATA - Abu Bakar (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
ABSTRACTBailiff is part of the implementation of its work in examining and prosecuting civil cases, has a no less important role with other officials in court, because its existence is treated since before the start of the trial so that the execution of court decisions. As a judicial officer presence, stipulated in the legislation, such as the common law courts, religious courts, administrative courts of the State, while the working set in procedural law (HIR / RBg)In Article 41 of Law - Law No. 8 of 2004 states that the District Court bailiff is appointed and dismissed by the Supreme Court upon the recommendation of the Chairman of the District Court is concerned, while the Bailiffs Substitutes shall be appointed and dismissed by the Chairman of the District Court besangkutan. while becoming a substitute bailiff, a candidate must be experienced at - least three (3) years as a Public Servant civil (PNS) it is stipulated in Article 40 of Law - Law No. 8 of 2004